2015
DOI: 10.1002/cyto.b.21244
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of neutrophilic CD64 and monocytic HLA‐DR: A novel parameter in diagnosis and prognostication of neonatal sepsis

Abstract: Objective: Approaches to monitoring of sepsis have traditionally relied upon the pro-inflammatory component of the sepsis response. This study evaluated the diagnostic and prognostic potential of the ratio of neutrophilic CD64 (nCD64) and monocytic HLA-DR (mHLA-DR) median fluorescence index in monitoring of neonatal sepsis.Methods: Blood from 100 neonates suspected of sepsis and 29 healthy controls was collected on clinical suspicion of sepsis, and the expression of nCD64, mHLA-DR was evaluated by Flow Cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Collectively, these findings suggested that S100A8/S100A9 are negative regulators for the expansion of both human DR 2 Mos and murine CD11b + /Gr-1 int /Ly6G 2 /Ly6C hi cells at birth. In human newborns, DR 2 Mos have been shown to be expanded in late-onset neonatal sepsis (LONS) (50,(54)(55)(56). These studies with LONS were performed during days 3 to 9 of life, which is when DR 2 Mos in healthy neonates are no longer expanded (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings suggested that S100A8/S100A9 are negative regulators for the expansion of both human DR 2 Mos and murine CD11b + /Gr-1 int /Ly6G 2 /Ly6C hi cells at birth. In human newborns, DR 2 Mos have been shown to be expanded in late-onset neonatal sepsis (LONS) (50,(54)(55)(56). These studies with LONS were performed during days 3 to 9 of life, which is when DR 2 Mos in healthy neonates are no longer expanded (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First reports in neonatology/pediatric sepsis indicate interesting results as similar immune alterations seem to be associated with poor outcome and/or HAI risk (decreased mHLA‐DR, decreased lymphocyte cytokine production, lymphopenia) . As sepsis remains a major cause of death in pediatrics, further investigations in immunological monitoring appear of major importance.…”
Section: Emerging Fieldsmentioning
confidence: 98%
“…The objective was to associate neutrophil CD64 expression with CD8 T‐cell activation, CD4 T‐cells numbers, and relate the above to HIV and HCV replications. They report overexpression of CD64 on neutrophils in co‐infected individuals . It is in line with HIV infection and corresponding up‐regulation of neutrophil CD64 expression.…”
Section: Neutrophil Cd64 Expression and Co‐infection With Hiv And Hcvmentioning
confidence: 65%
“…A flow cytometric application to study the impact of T‐cell activation associated with viral co‐infection with HIV and hepatitis C. Morquin, et al describe CD64 expression on neutrophils and developed a method to study the role of dual viral infection on this cell type using a protocol derived from one used for neonatal sepsis . The objective was to associate neutrophil CD64 expression with CD8 T‐cell activation, CD4 T‐cells numbers, and relate the above to HIV and HCV replications.…”
Section: Neutrophil Cd64 Expression and Co‐infection With Hiv And Hcvmentioning
confidence: 99%